Dampak Transformasi Digital Terhadap Persaingan: Peluang dan Tantangan pada Bisnis Adlya Olshop - Dianrana, Dianrana (Teewan Journal Solutions, 2025)
Digital transformation has changed market dynamics and consumer behavior, which has had a significant impact on online stores such as Adlya Olshop. This research aims to analyze the relative market share position of Adlya Olshop compared to its closest competitors using the BCG Matrix. The research results show that Adlya Olshop has a relative market share of 0.71, indicating an unfavorable position in the household appliance market. Based on these findings, this research recommends a number of strategies to increase competitiveness, including increasing marketing efforts through creative campaigns and the use of social media, sustainable product innovation, and training for resellers. In addition, regular evaluation of the product portfolio and increasing customer engagement through loyalty programs are also considered important. By implementing these strategies, it is hoped that Adlya Olshop can increase market share and business sustainability in the long term. This research provides valuable insight for business owners in facing increasingly competitive market challenges.